Butea monosperma: An Ornamental Plant to Precious Herb - A. V, Shrirao (International Journal of Pharmaceutical & Biological Archive, 2017)
Since ancient times plants are used for their medicinal and cosmetic properties. India has well-recorded and well practiced knowledge of traditional herbal medicine. Butea monosperma popularly known as Flame of the Forest, Dhak, Palash or â€˜Bastard teakâ€™ which has immense potential and appears to have a broad spectrum of activity on several ailments. Previous phytochemical examination of this plant indicated the presence of various constituents some of these are Cajanin and isoformononetin; Stigma sterol; Butin; two known flavonoids, isobutrin (3, 4, 2’, 4’-tetrahydroxychalcone-3, 4’-diglucoside), and the less active butrin (7, 3’, 4’-trihydroxyflavanone-7, 3’-diglucoside); free sugars and free amino acids and (-)-3-hydroxy-9-methoxypterocarpan[(-)-medicarpin which were isolated from stem-bark extract; bark; seeds; flower; the petroleum ether extract of flowers and petroleum and ethyl acetate extract of stem bark. Many reported pharmacological properties include anthelmintic, anticonceptive, anticonvulsive, antidiabetic, antidiarrhoeal, antiestrogenic and antifertility, antiinflammatory, antimicrobial, antifungal, antibacterial, antistress, chemopreventive, haemaggultinating, hepatoprotective, radical scavenging, Thyroid inhibitory, antiperoxidative and hypoglycemic effects and wound healing activities. Other then this Ayurvedic herbal medicine which was prepared from Piper longum (Pippali) and Butea monosperma (Palash) has significant activity against Giardiasis.